Integrated uncertainty in knowledge modelling and decision making : 6th International Symposium, IUKM 2018, Hanoi, Vietnam, March 15-17, 2018, Proceedings /: 6th International Symposium, IUKM 2018, Hanoi, Vietnam, March 15-17, 2018, Proceedings. (2018) - Unknown
No abstract available